INTERVENTIONS ON DRUG AND ALCOHOL ABUSE AMONG STUDENTS IN SECONDARY SCHOOLS IN NYERI CENTRAL SUB-COUNTY, NYERI COUNTY, NYERI COUNTY, KENYA - Kahuthu, Lucy Wangui; J. Kathuri, Prof. Nephat; Thuba, Ms. Esther (IJRDO - Journal of Business Management, 2017)
Alcohol and drugs pose special problems for students. According to Mutumi (2013), the average student who has one drink a day earns a GPA at only a C-level, and grades plummet with higher consumption. The purpose of this study was to explore the interventions of alcohol and drug abuse among the students in secondary schools in Nyeri Central Sub-County, Nyeri County, Kenya. It was also established that individual guidance and counselling techniques were scarcely practised in the area while NACADA hardly visited the area. The researcher recommended that the parents in the area of study should be role models to their children so as to discourage drug and alcohol abuse, counsellor teachers should be encouraged to extensively use individual counselling which has been shown to be more effective than group counselling